ANALISIS PENGARUH MOTIVASI, KEMAMPUAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK RIAU KEPRI CABANG BATAM - Mardana, Fauzi Yose (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to analyze and examine the influence of motivation, ability and discipline on the performance of employees working at PT Bank Riau Kepri Branch in Batam, either simultaneously or partially.The population in this study is the Employee of PT.Bank Riau Kepri Branch in Batam, amounting to as many as 88 people. Data collection using saturated sampling so that the sample amounted to 88 people. While the data collection techniques used were through interviews and questionnaires. To determine the magnitude of the relationship and the influence of independent variables on the dependent variable used method Regression Analysis Model. Meanwhile, to test the hypothesis using a statistical test. The results showed that the statistical calculation results obtained multiple correlation coefficient (R) with a value of 0.582 and the results of the coefficient of determination (R2) of 33.9% means that the influence of variable motivation, ability and discipline to performance is at 33.9%, and other variables that affect the performance of 66.1% variable. The significance of the influence of motivation, ability and discipline to the performance can be shown from the value of Fcount is greater than Ftable at level Î± = 5%. The results showed that the F count = 14,338 greater than the F table = 2.71. From the figure then the hypothesis H0 is rejected and H1 is accepted, which means the higher the level of motivation, ability and discipline, the higher the employee performance PT.Bank Kepri Riau branch in Batam. Partial test showed that the largest partial determination coefficient value contained in the variable ability by 46.1% to 0,000 sig.ability value, tcount = 4.231 > ttable = 1.633. These results indicate that the capability variable has the most dominant influence on the performance of PT Bank Riau Riau Batam Branch.Key Word : Motivation, Ability, Discipline, Employee Performance